Effects of Local Microorganisms (MOL) from Stale Rice and Palm Oil Boiler Ash on the Growth and Yield of Shallots (Allium ascalonicum L.) - Nursyva Alvira Sumara; Desi Sri Pasca Sari Sembiring; Hanifah Mutia Zaida Ningrum Amrul (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
The purpose of this study was to determine how the application of Local Microorganisms (LOM) from stale rice and oil palm boiler ash impacts the growth and production of shallots (Allium ascalonicum L.) and to determine the interaction between the two treatments. Shallots are a horticultural commodity with high economic value, so efforts are needed to increase production through the use of environmentally friendly organic materials. The study used a factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was LOM from stale rice with four levels (0, 20, 40, and 60 ml/L water/plot) and the second factor was oil palm boiler ash with four levels (0, 500, 1000, and 1500 grams/plot), resulting in 16 treatment combinations and 48 experimental plots. The parameters observed included plant height, number of leaves, number of tillers, fresh weight of bulbs, dry weight of bulbs, and bulb diameter. If there was a significant effect, the data were tested using analysis of variance (ANOVA). This research is expected to produce scientific data on the use of organic waste as an environmentally friendly fertilizer alternative.